Penerapan Akuntansi Publik dalam Pertanggungjawaban Kinerja Instansi Pemerintah di Kantor Koperasi Usaha Kecil Kabupaten Mandailing Natal - Abdul Nasser Hasibuan; Ali Hardana; Lismawati Hasibuan; Try Wahyu Utami; Sulaiman Efendi Siregar (Universitas Nusantara PGRI Kediri, 2023)
The term governance is actually an old term that was re-popularized by the World Bank in 1992 in its report entitled Governance and Development. The World Bank underscored that governments are the source of development failures. A great government will result in bad governance.